Duchenne muscular dystrophy: case series of rare inherited muscular disorder - Dewi, I. Gusti Ayu Sri Mahendra; Seputra, Desak Made Cittarasmi Saraswati (International Journal of Advances in Medicine, 2022)
Duchenne muscular dystrophy (DMD) is a rare muscular disorder caused by mutation of gene encoding dystrophin protein which required for maintaining muscle stability during contraction. DMD occurs in 1 in 5000 male live births and characterized by progressive muscular weakness associated with motor development delay, loss of independent ambulation, respiratory failure, and cardiomyopathy. We present a case series of 3 DMD patients who were diagnosed at Prof. dr. I.G.N.G. Ngoerah general hospital, Denpasar over a period of four years (2019-2022). Clinical manifestation of patients includes progressive weakness of lower extremities and difficulty to stand up from sitting position. Physical examination revealed pseudohypertrophy of calf, winged scapula, positive Gower’s sign, and waddling gait in all three cases. Supporting examination showed an increase of alanine transaminase and aspartate transaminase 5.6 times and 6.1 times the upper limit of normal, respectively. Definitive diagnosis of all patient was made based on immunohistochemistry staining which revealed an absent of dystrophin protein around muscle membrane.